QUATERNION NUMBERS TO ’ PLATE SOLVING THE QUADRATIC EQUATION - Mamajonov JD; Ismailov.MX; Mukhtorov T.Sh. (Galaxy International Interdisciplinary Research Journal, 2023)
The quadratic equation is solved using the operations defined in the set of quarternion numbers. The quadratic equation was solved in a special case, and its roots were found. The theorem on the solution of the quadratic equation is given, the formula for finding the square root of the number of quarternions is given.